The Impact of Temperature and Frying Time on Tempe Chips’ Quality and Consumer Acceptance: The Impact Of Temperature And Frying Time On Tempe Chip’s Quality And Consumer Acceptance - Shaf Rijal Ahmad; Mona Nur Moulia; Sevina Lorenza Varton (Fakultas Teknologi Pangan dan Agroindustri, Universitas Mataram, 2022)
As the main process in tempe chip production, frying can change food properties. This change will influence product quality and consumer acceptance. Temperature and frying time are one of the factors that affect the frying process. Therefore, it is important to understand the optimum temperature and length of time to produce tempe chip that is accepted by consumers. The aim of this research was to know the impact of temperature and length of frying time on water content, protein, crispiness, and consumer acceptance of this chip. This research applied a combination of temperature and frying time that are 140 oC, 150 oC, and 160 oC, and 3, 5, and 7 minutes. The analyzed parameter are water content, protein, and texture. This study also involved an organoleptic test: color, taste, aroma, and crispiness. This study shows that temperature and frying time affect the tempe chip characteristics. The best tempe chip based on its consumer acceptance was the chip that was fried at 160oC in 7 minutes (T3t3). The average acceptance score from T3t3 treatment was 4,2 and the characteristics of this tempe chip were: water content 4,09%; protein content 9,53%; and compression 0,87 N/cm2.